RULES AND METHOD OF SUPPORTING THE DECISION-MAKING REGARDING THE POSSIBILITY OF EXTRACORPOREAL FERTILIZATION (Computer systems and information technologies, 2022)
Considering the impossibility of applying for the paid services of a lawyer in most medical clinics, the legal correctness of decisions regarding the provision of various medical services can be significantly increased by a decision support system or technology regarding the possibility of providing medical services – at the expense of providing a conclusion on the possibility or impossibility of providing this or that medical service, taking into account civil legal grounds.The conducted analysis proved that none of the known systems/technologies are intended to support decision-making regarding the possibility of providing the extracorporeal fertilization, taking into account civil legal grounds. Although the use of such cross-disciplinary systems/technologies can significantly increase the correctness of the decision from a legal point of view, protect the doctor and the patient from legal collisions, provide an opportunity for a quick and free check of the presence of all significant conditions from a legal point of view, as well as recommendations for further implementation or non-implementation of extracorporeal fertilization procedures.The article develops rules and method of supporting the decision-making regarding the possibility of extracorporeal fertilization based on the civil legal grounds, which reflect the peculiarities of decision-making on whether or not to carry out extracorporeal fertilization based on the assessment of the sufficiency of information (compliance with requirements) for such a procedure, ensure adaptation to the specifics of the subject area and is a theoretical basis for the development of a decision-making support system/technology regarding the possibility of providing the extracorporeal fertilization, taking into account civil legal grounds.The developed rules and method ensure: verification of the agreement for the provision of extracorporeal fertilization services for the fulfillment of all essential conditions for the provision of in vitro fertilization from the point of view of civil legal grounds without the participation of legal experts, which ensures the possibility for medical clinics to comply with the requirements of current civil legislation without paying for the services of hired lawyers; a conclusion on the possibility or impossibility of providing the extracorporeal fertilization from the point of view of the civil legislation of Ukraine.The direction of the authors' future research is the realization of the subsystem of information technology for medical decision-making support taking into account civil legal grounds in the form of web-oriented software based on the developed method of supporting the decision-making regarding the possibility of extracorporeal fertilization taking into account civil legal grounds.
Keywords: rules of determining the possibility of extracorporeal fertilization considering civil legal grounds; method of supporting the decision-making regarding the possibility of extracorporeal fertilization taking into account civil legal grounds; agreement on the provision of extracorporeal fertilization services